2019
DOI: 10.21294/1814-4861-2019-18-1-50-55
|View full text |Cite
|
Sign up to set email alerts
|

Activation of interferon-α signaling by resveratrol, genistein and quercetin

Abstract: Resveratrol, genistein and quercetin from the group of polyphenols from secondary plant metabolites reveal cancer preventive and antivirus effects realized via their pleiotropic influence on the different macromolecules in cells. These compounds can interact with DNA without the formation of covalent bonds. This process is usually followed by changes in spatial, physical-chemical and structural DNA characteristics that can result in disfunction of DNA metabolism enzymes and chromatin destabilization. Similar e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…In addition, the researchers also reported that a STING agonist known as diABZI significantly inhibits SARS-CoV-2 infection by potentiating an innate immune response involving IFN signaling ( Li et al, 2021 ). Similarly, phytochemicals such as resveratrol, genistein, and quercetin have shown a dose-dependent stimulatory role on IFN signaling in the human HeLa cell lines ( Vlasova et al, 2019 ). Interestingly, the antidiabetic and anti-COVID-19 potential of these compounds has been reported earlier in this review.…”
Section: Covid-19 and Dm: Potentials And Challenges On The Use Of Her...mentioning
confidence: 99%
“…In addition, the researchers also reported that a STING agonist known as diABZI significantly inhibits SARS-CoV-2 infection by potentiating an innate immune response involving IFN signaling ( Li et al, 2021 ). Similarly, phytochemicals such as resveratrol, genistein, and quercetin have shown a dose-dependent stimulatory role on IFN signaling in the human HeLa cell lines ( Vlasova et al, 2019 ). Interestingly, the antidiabetic and anti-COVID-19 potential of these compounds has been reported earlier in this review.…”
Section: Covid-19 and Dm: Potentials And Challenges On The Use Of Her...mentioning
confidence: 99%